The applications of Hankel transform to the computation of nearfields of circular baflled sources - WYRZYKOWSKI, R.; CZYRKA, A. (Archives of Acoustics, 1993)
In the present paper we give a new method of computation of near sound fields emitted by baffled circular sources. We have applied the Hankel transform and King's integral. Two examples were calculated - namely the piston with uniform velocity distribution and membrane for different values of the rate of the speed of elastic waves in the membrane to the speed in the medium.